Relative intensity noise study in two mode quantum dot laser - Horri, Ashkan; Mirmoeini, Seyedeh Zahra; Faez, Rahim (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this paper, for the first time, we present a semiclassical noise model for InAs/GaAs quantum dot (QD) laser considering two photon modes, i.e., ground and first excited states lasing. This model is based on the five level rate equations. By using this model, the effect of temperature variations on relative intensity noise (RIN) of QD laser is investigated. We find that the RIN significantly degrades when excited state (ES) lasing emerges at high temperature. Furthermore, we investigate the influence of the quantum dot numbers on the RIN properties.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 961-970
Keywords: optyka; relative intensity noise; quantum dot laser; rate equations